Influence of oxidation on leaf decomposition in acid mine water - Mohasoa, Bongani Peter (My University, 2017)
Acidification of freshwater systems by Acid Mine Drainage (AMD) is a persistent risk to aquatic ecosystems in South Africa, particularly in Gauteng and Mpumalanga. From several studies that have been conducted, it is clear that AMD has profound effects on aquatic life and functionality of the ecosystem. One of the ecosystem processes affected by AMD is the decomposition process. It has been established that AMD-affected streams inhibit the decompositon process. [Abbreviated Abstract. Open document to view full version]
Thesis (M.Sc.)--University of the Witwatersrand, Faculty of Science, School of Animal, Plant and Environmental Sciences, 2017.
Keywords: Acid mine drainage--Environmental aspects; Acid mine drainage; Oxidation; Chemical weathering